Association Between Atopic Dermatitis, Asthma, and Serum Lipids: A UK Biobank Based Observational Study and Mendelian Randomization Analysis - Tang, Zhenwei; Shen, Minxue; Xiao, Yi; Liu, Hong; Chen, Xiang (Frontiers in Medicine, 2022)
Background: Both atopic diseases and dysregulation of serum lipids (SLs) add to significant health burden, but evidences about their association are inconsistent. Objective: This work is to evaluate the association between asthma/atopic dermatitis (AD) and SLs and investigate the potential causal relationship. Methods: A large-scale cross-sectional study based on the UK Biobank (UKB) and then examined the casual relationships between SLs with asthma/AD based on a Mendelian randomization (MR) analysis. Results: A total of 502505 participants were included in analysis. After full adjustment, AD was associated with lower TG (β=-0.006; 95%CI, -0.010 to -0.002; P=0.006), lower LDL (β=-0.004; 95%CI, -0.006 to -0.002, P<0.001), and lower TC (β=-0.004; 95%CI, -0.005 to -0.002; P<0.001) but insignificantly correlated to HDL(P=0.794). Asthma was also inversely correlated to TG (β=-0.005; 95%CI, =-0.007 to -0.003; P<0.001), LDL (β=-0.003; 95%CI, -0.004 to -0.002; P<0.001), and TC (β=-0.002; 95%CI, -0.003 to -0.002; P< 0.001), but was positively correlated to HDL (β=0.004; 95%CI, 0.003 to 0.005; P<0.001), respectively. In subsequent MR analysis, both allergic diseases and asthma showed a protective effect on TC. Allergic diseases, asthma, and AD all showed a negative effect on LDL. Conclusion: Collectively, we identify a protective causal effect of allergic diseases on serum lipids, as well as a potentially positive association of HDL with asthma. Owing to the largest sample size and the application of IVs in causal inference, this study will provide a robust evidence for the management of asthma and AD and the prevention of dyslipidemia.